2021
DOI: 10.1186/s40658-021-00426-y
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence with deep learning in nuclear medicine and radiology

Abstract: The use of deep learning in medical imaging has increased rapidly over the past few years, finding applications throughout the entire radiology pipeline, from improved scanner performance to automatic disease detection and diagnosis. These advancements have resulted in a wide variety of deep learning approaches being developed, solving unique challenges for various imaging modalities. This paper provides a review on these developments from a technical point of view, categorizing the different methodologies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 182 publications
0
18
0
Order By: Relevance
“…Nowadays, artificial intelligence (AI) deep learning is increasingly being introduced to improve the acquisition performance and the image quality of reconstructed images [24], especially for sparse PET configurations [25]. This can be done using a trained convolutional neural network (CNN) to predict from low count reconstructions the high count reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, artificial intelligence (AI) deep learning is increasingly being introduced to improve the acquisition performance and the image quality of reconstructed images [24], especially for sparse PET configurations [25]. This can be done using a trained convolutional neural network (CNN) to predict from low count reconstructions the high count reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…DL has achieved robust performance in medical elds such as radiology, pathology, and dermatology, which are similar to ophthalmology. [24][25][26] In ophthalmology, DL systems have been shown to accurately detect diabetic retinopathy, age-related macular degeneration, cataract, and glaucoma. [27][28][29][30] Brown [31] created a fully-automated DL system for normal/pre-plus/plus disease using convolutional neural network (CNN) based on 5,511 retinal images, AUC achieved 0.98 for plus diseases, compared with senior ophthalmologists, the DL system also showed strong advantages.…”
Section: Recurrence Rate Complicationsmentioning
confidence: 99%
“…Smoothing lters used to reduce image noise have the tradeoff of degrading resolution. Additionally, many studies have reported improving nuclear medicine image quality using deep learning [9][10][11][12][13][14][15]. These reports mainly used tomographic imaging techniques, such as SPECT and positron emission tomography.…”
Section: Introductionmentioning
confidence: 99%